Nonlinear surface-wave excitations in the Bénard-Marangoni system - Kraenkel, R. A. [UNESP]; Pereira, J. G. [UNESP]; Manna, M. A. (American Physical Society (APS), 1992)
We examine the appearance of surface waves governed by Burgers and Korteweg-de Vries equations in a shallow viscous heated fluid. We consider waves triggered by a surface-tension variation induced by both temperature and concentration gradients. We also establish the range of parameters for which the above-mentioned equations appear. © 1992 The American Physical Society.